Calculation method of thrust force of the embedded stabilizing piles under the overtop-sliding failure mode - Yuping YAN (Shuiwen dizhi gongcheng dizhi, 2023)
Embedded piles act as an optimization structure compared with the traditional stabilizing pile. The determination of the thrust on the loading section is based mainly on the model test and numerical simulation, and there is a lack of in-depth theoretical analysis. For the bedrock-talus landslide reinforced by embedded piles, according to the potential overtop-sliding failure mode, the slide surface can be divided into top and bottom sections by the position of pile top, and the horizontal resultant force of the top section can be obtained by integration, which is the so-called thrust of the embedded section. Similarly, the force on the bottom section of the overtop-sliding surface can also be obtained. Based on the limit equilibrium theory, the force analysis of the sliding mass enclosed by the bottom sliding surface and the load section of the pile can be carried out, and the thrust on the loaded section can also be obtained. Example analyses show that the thrust of the embedded section and the loaded section obtained by the theoretical method are very consistent with the results of FLAC3D, the resultant force of the loading section decreases nonlinearly with the increase of the ratio, while the resultant force of the embedded section presents an opposite trend. With the increase of the embedded ratio from 0 to 0.67, the thrust ratio of embedded section and loading section increases slowly from 0 to 0.3−0.5. With the increase of embedded ratio from 0.67 to 0.8, the ratio increases sharply to 1.47−2.12. Generally, the thrust of embedded section is less than that of loaded section. The theoretical research of the thrust of the embedded pile is of great practical significance for the optimization of the pile internal force and the determination of the pile embedded depth, which will promote the further application of this structure.